Metode Show And Tell: Peningkatan Kecerdasan Linguistik Anak Usia Dini - Nadia Maghfira Rahmah; Mustika Dewi Muttaqien (STAI Al-Hamidiyah Jakarta, 2025)
This research based on the factors of children in group B who are still not in accordance with their language development and want to improve the linguistic intelligence of children aged 5-6 years. Because from the result of observations at TK Kebon Alam Islami when the learning activities were taking place there were around 6 children whose pronunciation of words was not clear were not able to compose sentence correctly and were not able to describe something. Teachers must create interesting and fun learning so that children’s linguistic intelligence improve properly. The purpose of this study was determined the application of the show and tell method and to determine to increase in linguistic intelligence through the show and tell method. The research method used is Classroom Action Research. The subject consisted 8 children in the class. Data collection was carried out by observation, data collection instruments, and documentation. In this study there were 2 cycles and in each cycled there were 2 meetings. From the data analysis, the result is in the pra-cycle assessment indicators have only reached 33.33% with the criteria for starting to develop. Cycle I reached 63,02% with criteria of developing as expected. Cycle II reached 79,16% with very well develop criteria. After calculating the effort to improve linguistic intelligence of children aged 5-6 years through the show and tell methode increase and has achieved all the indicator set. It can be concluded that the show and tell methode can improve linguistic intelligence in group a childrens at TK Kebon Alam Islami Depok.